Analisis Eksegesis Kata Dunamin dalam Markus 6:5 Dikaitkan Dengan Pelayanan Yesus dan Pertumbuhan Iman - Subriyanto, Subriyanto; Pardosi, Milton Thorman (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to conduct an exegesis analysis of the word “dunamin” in Mark 6:5 and relate it to the ministry of Jesus towards the growth of faith of believers. In general, the word miracle is considered as an act of God or a miracle of healing, while the word miracle in Mark 6:5 is more than the real meaning. The expression “δύναμιν” in Mark 6:5 translates as “power” or ‘strength’ of God greater than the miracle “θεραπεύω” and has a deep meaning in the context of Jesus' ministry. In Mark 6:5, it is stated that Jesus could not perform a single miracle in Nazareth because of their unbelief. This study uses a qualitative approach with the method of exegesis of the Greek text of the New Testament. The result of this analysis found that the limitation of the expression “dunamin” in this passage does not reflect the weakness of Jesus' power, but rather shows the close relationship between faith and acceptance of God's work. The implication of this finding is that Jesus' ministry is not only about the unilateral delivery of power, but awaits an active response in the form of faith from the recipient, the acceptance of which is called “repentance”. Thus, repentance is an important factor in opening up space for the work of God's power to work in the lives of Christians in the growth of faith.